Ecological Park Falls of Rio Bonito: Perceptions of visiting frequency - Salgado, Mariel de Carvalho; Figueiredo, Paulo Henrique; Boldrin, Karina Volpi Furtini; Sousa, Rafael de Brito; Paiva, Patricia de Oliveira (Ornamental Horticulture, 2016)
The Ecological Park “Falls of Rio Bonito” is the unique ecological park located in Lavras region. This park has as purpose the regional fauna flora and water resources protection, environmental education, recreation and scientific research. However, the frequency of this park is decreasing over the time. Due to its great importance for Lavras, especially for eco-environmental aspects, a survey was conducted in order to identify city inhabitants impressions related to this area. The survey used structured questionnaires with direct questions. Four hundred people of all Lavras neighborhood were interviewed randomly. The park is visited most by the people who has middle-level education, family income greater than R 2,100.00 (minimum salary based on R678.00). The most prominent attractions in the visitors’ view are the nature elements (waterfall: 27.76%, and tracks: 21.35 %). A part of the visitors (28.11%) had visited only once the park, and they alleged that the main reason why they did not return is constraints (41.8%). Among the respondents, 22% have heard about the park, but never visited it, due to constrains (45.5%) and lack of opportunity (17%). Only 7.75% of the respondents did not have knowledge about the park. The Park Falls of Rio Bonito has been sparsely attended due to the lack of ecological activities, constraints, the distant location and the park entrance fee.